Piezoelectric energy harvesting using poly (Vinylidene Difluoride-Trifluoroethylene) - Bhavanasi, Venkateswarlu (2016)
Mechanical energy is available almost everywhere and at all the time in the ambient environment. Piezoelectric materials converts the ambient mechanical energy into useful electrical energy which can be used to realize the self-powered electronic devices and sensors. Ferroelectric/piezoelectric polymer, poly (vinylidene difluoride - trifluoroethylene) [PVDF-TrFE], is flexible and can sustain larger strains and strain rates (/impact stress) compared to inorganic counter-parts, making it attractive for harvesting energy from the mechanical vibrations. Yet, the piezoelectric energy harvesting ability of these polymers are unsatisfactory because of lower piezoelectric coefficients and Young’s modulus of the PVDF-TrFE compared to inorganic counterparts. Various strategies are employed to improve the energy harvesting performance of PVDF-TrFE by improving the properties such as piezoelectric coefficient, Young’s modulus and by combining the electrostatic energy harvesting along with piezoelectricity. Firstly, combining the PVDF-TrFE films with graphene oxide (a negatively charged material with high modulus) not only enable to harvest electrostatic component along with piezoelectricity but also improves the Young’s modulus and creates residual stress (/stress gradient) into the PVDF-TrFE films. This leads to the enhanced energy harvesting performance of bi-layer films over PVDF-TrFE films alone. Secondly, by synthesizing the one dimensional nanostructures of PVDF-TrFE (nanotubes/nanowires), it is obtained oriented crystal structure corresponding to (110) planes (along the length of the nanotubes) and hence lower coercive fields and higher piezoelectric coefficient values compared to film counterpart. Higher piezoelectric coefficients along with high surface area and strain confinement in the 1-D nanostructures lead to the improved energy harvesting performance over PVDF-TrFE films. Furthermore, a methodology is provided to control the alternating current (AC) type nature of the output of the piezoelectric energy harvesting devices. By employing a ferroelectric polarization charge in series with the piezoelectric energy harvesting device, an asymmetric voltage output with reduction in the voltage at one end of the AC peak is observed, a step towards realizing the DC type voltage output from the futuristic piezoelectric energy harvesting devices. The work provided here is advantageous to develop an efficient piezoelectric energy harvester and hence to develop self-powered electronic devices or sensors.